Associations between daily dietary carbohydrate intake and TIR in adults with type 1 diabetes - Cai, Yunying; Li, Xi; Xiong, Xin; Zhang, Lun; He, Jianfeng; Su, Heng (Frontiers in Nutrition, 2025)
ObjectiveTo assess the association between daily carbohydrate (CHO) intake and glycemic control in adults with type 1 diabetes (T1D).MethodsPatients with T1D who received continuous glucose monitoring (CGM) to manage their blood glucose levels were enrolled in the study. A dietitian analyzed dietary components, including carbohydrate, protein, and fat percentages in the total dietary intake. Mean individual daily CHO intake (MIDC) and relative deviation from MIDC (< 80% low; 81%−120% medium, >120% high CHO consumption) were compared with parameters of glycemic control assessed by CGM.ResultsRecords from 36 patients [11 male, 25 female; age 39.5 ± 13.9 years; HbA1c 9.0 ± 2.8% (75 ±31 mmol/mol)]. Provided 356 days of data for a total of 1,068 meals. Time in range (3.9–10 mmol/l) for low, medium, and high CHO consumption was 81.6 (70.96, 90.28)%, 74.65 (59.55, 84.9)%, and 64.58 (51.04, 77.78)%, respectively (P < 0.001). Time above range (>10 mmol/L) was 9.55 (1.39, 17.95)%, 10.42 (2.78, 27.43)%, and 27.08 (11.46, 47.92)%, respectively (P < 0.001). There was no between-group difference for time in hypoglycemia (< 3.9 mmol/L; P = 0.136). After adjusting for HbA1c, total calorie intake, and total daily insulin dose, carbohydrate intake was negatively correlated with achieving TIR ≥ 70%.ConclusionsDaily CHO intake was inversely associated with glycemic control in adults with T1D. A carbohydrate energy percentage between 40% and 50% and a relatively low daily carbohydrate intake may be a strategy to optimize glucose control in suboptimal-controlled T1D in real-world settings.